2021
DOI: 10.1016/j.shaw.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Semiquantitative Health Risk Assessment of Occupational Exposure to Styrene in a Petrochemical Industry

Abstract: Background Styrene is one of the aromatic compounds used in acetonitrile–butadiene–styrene (ABS) producing petrochemicals, which has an impact on health of workers. Therefore, this study aimed to investigate the health risks of styrene emitted from the petrochemical industry in Iran. Methods Air samples were collected based on NIOSH 1501 method. The samples were analyzed by the Varian-cp3800 gas chromatograph. Finally, risk levels of styrene's health effects on employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Similar to the Chinese researchers, scholars in South Korea have also conducted a comparative study on a qualitative risk assessment method improved based on the COSHH model and a quantitative assessment improved based on USEPA model to evaluate health risks caused by 36 kinds of hazardous substances requiring management ( 68 ). In Iran, the results of a comparison study on health risk assessment on occupational exposure to styrene in a petrochemical industry using the USEPA model and the Singaporean model implied that the estimated health risk of exposure to styrene was higher in the EPA model than in the Singaporean model ( 69 ). Only a few studies included in this review were methodological optimization studies ( 45 , 50 – 52 , 70 – 72 ), which were conducted to improve the OHRA methods and provide insights for establishing OHRA methods suitable for the workplace in China.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Chinese researchers, scholars in South Korea have also conducted a comparative study on a qualitative risk assessment method improved based on the COSHH model and a quantitative assessment improved based on USEPA model to evaluate health risks caused by 36 kinds of hazardous substances requiring management ( 68 ). In Iran, the results of a comparison study on health risk assessment on occupational exposure to styrene in a petrochemical industry using the USEPA model and the Singaporean model implied that the estimated health risk of exposure to styrene was higher in the EPA model than in the Singaporean model ( 69 ). Only a few studies included in this review were methodological optimization studies ( 45 , 50 – 52 , 70 – 72 ), which were conducted to improve the OHRA methods and provide insights for establishing OHRA methods suitable for the workplace in China.…”
Section: Discussionmentioning
confidence: 99%
“…In carcinogenic risk analysis, as slope factor (SF) values were available for both BD and ST (IUR value was available only for BD), we used exposure pathway expressed by calculating CDI to have the consistency between BD and ST in carcinogenic risk calculations. However, we have used the lowest available SF value for ST obtained from scientific literature 41 in accordance with the conservative risk assessment principle. SF value for ST used in our studies did not appear in the toxicological databases as the result of the lack of the agreement on confirmed SF and/or IUR value for ST.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of ST only RfC value was confirmed in the toxicological databases. In the case of the SF value for ST we used the value available in other research 41 , having in mind that so far there is no one agreed value. Banton et al 2019 48 reported that RfC value for ST for general population based on ototoxicity was estimated to be 6 ppm (about 25 mg m 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To control the sources of danger, and to achieve the purpose of gradually eliminating dangerous and harmful factors, so that production equipment and security facilities can be protected from damage, while the natural environment can also be well protected. [3] Production safety management is a component of safety science, which refers to the efforts of people to achieve the harmony of machinery, materials and environment in the production process. [4] Production managers make effective decisions and reasonable plans, make full use of effective resources, solve people's safety problems in the production process by organizing safety learning and ISSN 2706-655X Vol.4, Issue 1: 37-45, DOI: 10.25236/IJFET.2022.040107…”
Section: Enterprise Safety Managementmentioning
confidence: 99%